Rubén Darío and Claude Debyssy. The Submerged Cathedral and the Symphony in Grey Major - Rojas González, José Manuel (2008)
This paper's main purpose is to establish a link between the poetic work of a writer and the composition of a musician. Can you work with literature and music and create a link between them? It is a question that has been asked frequently and which we will try to answer affirmatively.